2003
DOI: 10.1002/cne.10529
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the GDNF family receptors RET and GFRα1, 2, and 4 in subsets of motoneurons: A relationship between motoneuron birthdate and receptor expression

Abstract: Previous studies have demonstrated the expression of specific members of the glial cell line-derived neurotrophic factor (GDNF) receptor family alpha (GFRalpha) in subsets of motoneurons (MNs) in the developing mouse spinal cord. We examined the expression pattern of GFRalpha and RET in the avian lumbar spinal cord during the period of programmed cell death (PCD) of MNs by using double labeling in situ hybridization and immunohistochemistry. In the lateral motor column (LMC) of the lumbar spinal cord, a lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…Thus, Ret DN/+ mice have deficits in SPG neuron number, size and target innervation that are a combination of the defects observed in GDNF-and NRTN-null mice, supporting the hypothesis that persistent Ret signaling is required for both the formation and proper function of SPG neurons. The previous analysis of Ret -/-and ARTN -/-mice revealed that Ret signaling is also important for sympathetic neuron precursor migration and neuronal projections (Enomoto et al, 2001;Homma et al, 2003). In Ret DN/+ mice, we found that, in contrast to in ARTN-and Ret-null mice, the SCG was properly located and had normal axonal projections to its targets (Fig.…”
Section: Long-segment Distal Intestinal Aganglionosis In Ret Dn/+ Micesupporting
confidence: 48%
“…Thus, Ret DN/+ mice have deficits in SPG neuron number, size and target innervation that are a combination of the defects observed in GDNF-and NRTN-null mice, supporting the hypothesis that persistent Ret signaling is required for both the formation and proper function of SPG neurons. The previous analysis of Ret -/-and ARTN -/-mice revealed that Ret signaling is also important for sympathetic neuron precursor migration and neuronal projections (Enomoto et al, 2001;Homma et al, 2003). In Ret DN/+ mice, we found that, in contrast to in ARTN-and Ret-null mice, the SCG was properly located and had normal axonal projections to its targets (Fig.…”
Section: Long-segment Distal Intestinal Aganglionosis In Ret Dn/+ Micesupporting
confidence: 48%
“…Thus, even if motor neurons innervate the inappropriate muscle in older donor limbs, they most likely would be exposed to GDNF. This finding suggests that the expression of Pea3 in just three motor pools most likely reflects the pool-specific expression of GDNF receptor ␣ family members (Homma et al, 2003), rather than the restricted expression of GDNF in the target. The restriction of Er81 to the appropriate motor neurons following a variety of surgical manipulations that mismatched motor neurons and the periphery (Wang and Scott, 2004) suggests that Er81 expression is constrained by similar mechanisms, although the peripheral signals and their receptors remain to be elucidated.…”
Section: Restriction Of Ets Expression To Appropriate Motor Poolsmentioning
confidence: 94%
“…Pea3 expression is induced by GDNF, which is widely expressed in hindlimb muscles (Homma et al, 2003). Thus, even if motor neurons innervate the inappropriate muscle in older donor limbs, they most likely would be exposed to GDNF.…”
Section: Restriction Of Ets Expression To Appropriate Motor Poolsmentioning
confidence: 99%
“…Previous analysis of Ret-null and Artemin-null mice showed that Ret signaling is important for sympathetic neuron precursor migration and axonal projection (10,30). In these mutants, the SCG fails to migrate to its proper location, resulting in accompanying abnormalities in projections to the submandibular gland and muscles of the eye.…”
Section: Figurementioning
confidence: 99%